Rajasthans Third Five Year Plan Proposals - Planning Commission (Planning Commission, 1960)
According to the revised targets fixed for Rajasthan, we were required to raise Rs. 31 crore of resources as our contribution towards the financing of the Second Plan. As against this target, it is expected that we would have contributed Rs. 40-05 crore by the end of the Second Plan- Particular mention may be made of our effort in raising resources by additional taxation. As against the target of Rs. 11-00 crore, it is expected that our contribution by way of additional taxation would be about Rs. 13-50 crore. The following statement will indicate the targets fixed during the Second Plan and the likely results of our efforts
Proposals
Government of Rajasthan